FUCCI-Based Live Imaging Platform Reveals Cell Cycle Dynamics and Identifies Pro-proliferative Compounds in Human iPSC-Derived Cardiomyocytes - Murganti, Francesca; Derks, Wouter; Baniol, Marion; Simonova, Irina; Trus, Palina; Neumann, Katrin; Khattak, Shahryar; Guan, Kaomei; Bergmann, Olaf (Frontiers in Cardiovascular Medicine, 2022)
One of the major goals in cardiac regeneration research is to replace lost ventricular tissue with new cardiomyocytes. However, cardiomyocyte proliferation drops to low levels in neonatal hearts and is no longer efficient in compensating for the loss of functional myocardium in heart disease. We generated a human induced pluripotent stem cell (iPSC)-derived cardiomyocyte-specific cell cycle indicator system (TNNT2-FUCCI) to characterize regular and aberrant cardiomyocyte cycle dynamics. We visualized cell cycle progression in TNNT2-FUCCI and found G2 cycle arrest in endoreplicating cardiomyocytes. Moreover, we devised a live-cell compound screening platform to identify pro-proliferative drug candidates. We found that the alpha-adrenergic receptor agonist clonidine induced cardiomyocyte proliferation in vitro and increased cardiomyocyte cell cycle entry in neonatal mice. In conclusion, the TNNT2-FUCCI system is a valuable tool to characterize cardiomyocyte cell cycle dynamics and identify pro-proliferative candidates with regenerative potential in the mammalian heart.